CHA2DS2-VASc score and the risk of death in atrial fibrillation. (19th May 2022) - Aro, A; Haukka, J; Halminen, O; Putaala, J; Linna, M; Mustonen, P; Hartikainen, J; Airaksinen, J; Lehto, M
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Sigrid Juselius Foundation Background: Atrial fibrillation (AF) is recognized as a major public health problem due to increased mortality, morbidity and risk of stroke. Advanced age and burden of other comorbidities are potential contributors to AF development and adverse outcomes. Clinical risk factor based CHA2DS2-VASc score is widely used to assess thromboembolic risk in AF, but mortality risk associated with different CHA2DS2-VASc scores is not established. Purpose: Using data from a nationwide AF registry study including comorbidities and outcomes of unselected AF patients, we wanted to study whether CHA2DS2-VASc score could be useful in estimating prognosis in newly diagnosed AF patients. Methods: New-onset AF patients in Finland 2007-2017 were identified from comprehensive national registries. Comorbidities were gathered from individualized registry data on drug reimbursements and from ICD-10 diagnoses during hospitalizations and outpatient visits in primary and specialist care. These were used to create CHA2DS2-VASc risk score for each AF patient at cohort entry, including data on heart failure, hypertension, age, diabetes, stroke, vascular disease and sex. Patients were followed until the end of 2018 from the causes of death registry, which records every death in the country. All-cause mortality in each CHA2DS2-VASc category per 1000 person-years was determined, and relative risk (RR) of death according to the CHA2DS2-VASc category was calculated. Results: A total of 229 357 patients with new-onset AF (mean age 73.2 ± 13.2 years, 50.0% female) were identified. Distribution of CHA2DS2-VASc score among these individuals is shown in Table. Mortality increased significantly with rising CHA2DS2-VASc risk score points, as demonstrated in Table. Compared to CHA2DS2-VASc 0, those with 2 points had a RR 2.9 (95%CI 2.7-3.1), 3 points RR 5.0 (4.7-5.3), 4 points RR 8.0 (7.5-8.4), 5 points RR 11.0 (10.4-11.7) and >5 points RR 14.8 (14.0-15.7) for all-cause mortality. Conclusions: In new-onset AF, mortality increased drastically with increasing age and comorbidities as depicted in the CHA2DS2-VASc score. Besides assessing thromboembolic risk, CHA2DS2-VASc score seems to be useful in estimating survival of AF patients.